2006
DOI: 10.1038/modpathol.3800694
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the novel oncogene, SALL4, in lymphoma, plasma cell myeloma, and acute lymphoblastic leukemia

Abstract: CanadaSALL4, a newly identified zinc-finger transcriptional factor important for embryonic development, is mapped to chromosome 20q13. Previously, we reported that SALL4 was constitutively expressed in acute myeloid leukemia and SALL4 transgenic mice developed acute myeloid leukemia. In this study, we aimed to survey SALL4 protein expression in benign and neoplastic hematopoietic tissues in addition to acute myeloid leukemia using immunostaining with a polyclonal anti-SALL4 antibody. Primary hematological tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 34 publications
4
71
0
Order By: Relevance
“…In the literature, the only other types of non-germ cell tumors that were immunohistochemically positive for SALL4 staining were precursor B-lymphoblastic lymphoma and acute myeloid leukemia, whereas other types of hematolymphoid tumors were negative. 30 Distinction of these tumors from germ cell tumors can usually be made on clinical presentation, morphologic findings, and, in difficult cases, immunohistochemistry for pan B cell or myeloid leukemia markers.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the only other types of non-germ cell tumors that were immunohistochemically positive for SALL4 staining were precursor B-lymphoblastic lymphoma and acute myeloid leukemia, whereas other types of hematolymphoid tumors were negative. 30 Distinction of these tumors from germ cell tumors can usually be made on clinical presentation, morphologic findings, and, in difficult cases, immunohistochemistry for pan B cell or myeloid leukemia markers.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Morphologically, metastatic yolk sac tumor or other germ cell tumors should be easily distinguished from these entities. In difficult cases, an immunohistochemical panel including antibodies toward CD10, CD19, CD79a, and TDT for precursor B lymphoblastic lymphoma and myeloperoxidase, leukocyte common antigen (CD45), CD43, and CD34 for myeloid leukemia should help in making the distinction from germ cell tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SALL4 upregulates the expression of the oncogene Bmi-1 in human hematopoietic stem cells and leukemia cells (14). Numerous other studies have also revealed the oncogenic potential of SALL4 (5,6,15), indicating that SALL4 may be used as a diagnostic marker in human malignancies. However, there have been no studies investigating the sensitivity and specificity of SALL4 expression in the diagnosis of non-germ cell tumors (GCTs).…”
Section: Introductionmentioning
confidence: 98%
“…Currently, a considerable number of stem cell-associated markers have been identified (2,3). Numerous studies have revealed that Sal-like protein 4 (SALL4) and leucine-rich repeat-containing G-protein coupled receptor 5 (LGR5) are also involved in the tumorigenesis, development and metastasis of various tumors (5)(6)(7), and these proteins are expected to become potential diagnostic markers and therapeutic targets in cancer.…”
Section: Introductionmentioning
confidence: 99%